(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Key words: Gossypium hirsutum, Rooting, Transgenic cotton D.O.I. 10.3329/ptcb.v19i2.5442 Plant Tissue Cult. & Biotech. 19(2): 247-251, 2009 (December) - Short communication